Design and Implementation of Two-Wheeled Robot Control Using MRAC - Isdaryani, Feni; Salam, Rudi; Feriyonika, Feriyonika (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2021)
The control strategy for a two-wheeled robot is still continuously researched and developed due to its natural behavior (unstable and non-linear). In this research, the Model Reference Adaptive Control (MRAC) using the Lyapunov stability theorem was applied in a two-wheeled robot. MRAC was used to design adaptive controllers that work on the principle of adjusting controller parameters so that the actual output traces the output of the reference model, which has the same reference input. The adjusting mechanism was built to ensure stability and convergence from the adaptation errors. The verification experiment showed that with the adaptation gain γ1, γ2, γ3 are 1, 0.005 and 0.001 respectively, the response could follow the reference model with a rising time and settling time 0.27 s and 0.87 s, respectively.